The Use of Animated Videos in Preventing Anemia in Adolescent Girls - Julianawati, Tinta; Yana, Lusi; Aprilia, Dinda (Edumedia Solution, 2025)
Anemia is a serious public health problem and has an impact on the life cycle of adolescents, especially adolescent girls. Adolescent girls who suffer from anemia have limitations in the growth process, learning capacity, ability to focus on daily activities, are susceptible to infection, have a tendency to drop out of school, physical fitness levels, and work productivity. The risk of anemia in adolescent girls tends to increase with age and coincides with the teenage years when the growth process occurs most rapidly. The ages between 12 and 15 years, when nutritional needs are very high, are known to have a very high risk of suffering from anemia. One of the educational media that can be easily understood by adolescents is animated videos. The purpose of this community service is to increase knowledge about preventing anemia in adolescents. The activities carried out are in the form of education, using educational videos to prevent anemia in adolescents. The method used is socialization and health education to adolescent girls through videos and explanations of the consumption of iron tablets distributed to all adolescent girls. The location of the activity was carried out at SDN 001 Nongsa. The stages of the activity include the stages of preparation, implementation and reporting. Data from the results of community service activities showed an increase in the capacity of adolescent girls, showing a change of 22 points in the pre-post test education, HB level examination from 30 people. The examined adolescent girls who experienced anemia were 16 people (53%) and 14 people did not experience anemia. All adolescents showed high enthusiasm for this activity and hoped that anemia and nutritional status education activities could be carried out sustainably to improve the fitness and health of adolescent girls.